Contribution of collective attack tactics in differentiating handball score efficiency - Rogulj, N.; Srhoj, V.; Srhoj, L. (Collegium Antropologicum, 2004)
The prevalence of 19 elements of collective tactics in score efficient and score inefficient teams was analyzed in 90 First Croatian Handball League - Men games during the 1998-1999 season. Prediction variables were used to describe duration, continuity, system, organization and spatial direction of attacks. Analysis of the basic descriptive and distribution statistical parameters revealed normal distribution of all variables and possibility to use multivariate methods. Canonic discrimination analysis and analysis of variance showed the use of collective tactics elements on attacks to differ statistically significantly between the winning and losing teams. Counter-attacks and uninterrupted attacks predominate in winning teams. Other types of attacks such as long position attack, multiply interrupted attack, attack with one circle runner attack player/pivot, attack based on basic principles, attack based on group cooperation, attack based on independent action, attack based on group maneuvering, rightward directed attack and leftward directed attack predominate in losing teams. Winning teams were found to be clearly characterized by quick attacks against unorganized defense, whereas prolonged, interrupted position attacks against organized defense along with frequent and diverse tactical actions were characteristic of losing teams. The choice and frequency of using a particular tactical activity in position attack do not warrant score efficiency but usually are consequential to the limited anthropologic potential and low level of individual technical-tactical skills of the players in low-quality teams.